2023
DOI: 10.1108/ajb-01-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate and psychological capital for positive customer behavioral intentions in service organizations

Abstract: PurposeThe purpose of this paper is to articulate a synergic-mediated model of positive service behaviors enabled by what could be called a “psychosocial resource caravan” for improved customer behavioral intentions to help service organizations especially during coronavirus disease 2019 (COVID-19) crisis.Design/methodology/approachThis paper adopts a multi-level approach and is based on positive organizational behavior and occupational health and safety literature. An empirical study of synergic-mediated mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Workers were more likely to be workaholics [ 44 ], have high morale [ 83 ], and develop organisational citizenship behaviours [ 50 ] in a high PSC context. Moreover, adaptive and proactive work behaviours [ 88 ], creative problem solving [ 55 , 89 ], taking of personal initiatives [ 80 ], personal development [ 80 ], positive service behaviour [ 88 ], workaround [ 68 ], and service recovery performance [ 90 ] were more likely to be observed in high PSC work environment. Perhaps, managerial quality is one of the key benefits in a high organisational PSC context [ 64 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers were more likely to be workaholics [ 44 ], have high morale [ 83 ], and develop organisational citizenship behaviours [ 50 ] in a high PSC context. Moreover, adaptive and proactive work behaviours [ 88 ], creative problem solving [ 55 , 89 ], taking of personal initiatives [ 80 ], personal development [ 80 ], positive service behaviour [ 88 ], workaround [ 68 ], and service recovery performance [ 90 ] were more likely to be observed in high PSC work environment. Perhaps, managerial quality is one of the key benefits in a high organisational PSC context [ 64 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…High-quality work with manageable job demands, and adequate job resources were more likely in a high PSC work environment, where managers value and safeguard workers’ psychological health for improved well-being, safety and performance outcomes [ 18 , 59 , 66 ]. Thus, a high PSC context foster satisfaction of psychological needs, job satisfaction, job commitment, and mental health maintenance, which translate into improved productivity [ 58 , 88 , 89 ]. Basically, in such a PSC context, workers perceive that their well-being is a priority to managers, hence, become intrinsically motivated, which may lead to improved mental health and well-being [ 98 , 99 ], and positive performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, since PsyCap has been a concept of central interest of contemporary organizations owing to its positive work outcomes (Avey et al, 2011a, b;Newman et al, 2014a, b;Salanova and Ortega-Maldonado, 2019;Siami et al, 2023;Loghman et al, 2023), HR managers, scholars, practitioners and researchers must appreciate its vital role and encourage a conducive work environment that fosters PsyCap. To meet the dynamic needs of the customers IT/ITes IJPPM 73,6 employees need to enjoy their work, as the work in information pertains to innovation in the customer's organization.…”
Section: Discussionmentioning
confidence: 99%
“…Though intrinsic motivation is desirable, developing it is a Hercules task as it is not instrumental in nature and is Impact of PsyCap on multifaceted job performance inherent to individuals (Deci and Ryan, 2000;Delaney and Royal, 2017;Li et al, 2023). The strength-based approach toward work motivation can be one such way to foster intrinsic motivation as it is considered as a more organic approach (Martin, 2005;Mills et al, 2013;Donaldson et al, 2019;Siami et al, 2023). There is a paucity of work in this area, and scant studies have a deployed strength-based approach to engender intrinsic work motivation (Gupta and Shaheen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Kim [ 34 ] found that positive psychological capital and social support of special education teachers can regulate the impact of emotional labor on job burnout, and thus affect career happiness. Other studies have found that psychological capital and psychosocial safety atmosphere can improve the positive service behaviors of service workers towards work and customers [ 43 ], which promotes occupational health and safety. Therefore, the following hypothesis is proposed in this study:…”
Section: Introductionmentioning
confidence: 99%